THE ACADEMIC FORMATION AND THE JOB MARKET AT GYMS IN THE CITY OF PELOTAS (Fiep Bulletin - online, 2014)
Abstract: this article is part of a research about the work market - gyms in the city of Pelotas - and the professional formation of Physical Education. We use the resources of scientific initiation to create the bond between the research and the teaching process; both topics are interesting to the professional who is getting started at the job market.
Keywords: professional formation; job market; health